The Algorithm for the Study of Deep Femoral Vessels Using Ultrasound Duplex Angioscanning - R. E. Kalinin; I. A. Suchkov; E. A. Klimentova; I. N. Shanayev; R. M. Khashumov (Неотложная медицинская помощь, 2023)
The deep femoral vessels are the main branches/donor vessels of the femoral vessels. Their branches penetrate the entire array of muscles of the posteromedial group and descend almost to the popliteal region, so they are able to both largely compensate for blood flow disorders in obliterating atherosclerosis of the arteries of the lower extremities, and in the presence of an anastomosis with the popliteal vein, influence the course of acute and chronic vein diseases. The modern standard for studying the vascular system of the lower extremities is duplex scan, but it allows deep femoral vessels to be examined only in the ostium segment up to 5–6 cm.AIM OF STUDY To determine the patency and state of blood flow in the deep femoral vessels throughout the entire length using ultrasound duplex angioscanning.MATERIAL AND METHODS The analysis of the results of 30 computed tomograms and 100 ultrasound scans of patients (aged 20 to 85 years) who underwent routine examination of the vascular system of the lower extremities in a polyclinic setting was carried out. The study was performed according to the original method (Patent for invention No. 2751819).RESULTS In the upper third of the thigh, the deep femoral vessels are located most superficially, 2.3±0.15 cm from the skin surface and 0.5±0.08 cm from the posterior wall of the femoral artery. In the middle third of the thigh, the depth of the deep femoral vessels is 3.5±0.9 cm from the skin surface and 4.3±0.24 cm from the posterior wall of the femoral artery. The deep femoral vessels are located between the vastus medialis and adductor longus muscles closer to the femur. In the lower third of the thigh, deep femoral vessels are located at a distance of 4.3±0.4 cm from the skin surface and 1.8±0.5 cm from the posterior wall of the femoral artery. Therefore, for ultrasound examination, a linear probe is first used, which is placed along the projection line of the femoral vessels in the upper third of the thigh, and then the orifice of the deep femoral vessels is visualized. Next, a convex probe is used, and in the middle and lower third of the thigh, it is drawn along a line located 2 cm medially to the projection line of the femoral vessels, while the probe itself deviates posteriorly by ~ 15°.CONCLUSION The research algorithm helps increase the length of the areas of the deep femoral artery and vein available for research and help the physician choose the optimal method of treating the patient.